MODERASI BERAGAMA DALAM PERSPEKTIF AL-QUR’AN (Sebuah Tafsir Kontekstual di Indonesia) - Abdul Aziz (LP2M Universitas PTIQ Jakarta, 2021)
This article aims to explain that the Qur’an does not at all justify the practice of violence or extreme attitudes in the name of religion. On the contrary, the Qur'an encourages a balanced religious attitude between the practice of one's own religion (exclusive) and the religious practices of others who have different beliefs (inclusive). This study offers a solution through three basic principles in the Qur’an, namely the principle of universality, the principle of integration, and the principle of multiculturalism. This study uses library research which is descriptive in nature by referring to and taking the thoughts of both classical and modern commentators and referring to books, journals, articles that can support this writing. The results of this paper find that through a basic understanding of the principles of the Qur’an, someone who has an inclusive and radical understanding of religion will gradually give birth to an attitude of exclusiveness, mutual respect, acceptance and tolerance in social life